2019
DOI: 10.1038/s41524-019-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

Solving the electronic structure problem with machine learning

Abstract: Simulations based on solving the Kohn-Sham (KS) equation of density functional theory (DFT) have become a vital component of modern materials and chemical sciences research and development portfolios. Despite its versatility, routine DFT calculations are usually limited to a few hundred atoms due to the computational bottleneck posed by the KS equation. Here we introduce a machine-learning-based scheme to efficiently assimilate the function of the KS equation, and by-pass it to directly, rapidly, and accuratel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
204
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(227 citation statements)
references
References 40 publications
2
204
0
3
Order By: Relevance
“…ing of scalar fields such as the electron charge density. Machine-learning models for the charge density have been proposed based on the coefficients in a plane wave basis [16] -this is convenient due to orthogonality, but leads to poor transferability when considering flexible molecules, or learning across different molecular species -or based on direct prediction of the density on a realspace grid [17,36]. By expanding the density on an atomcentred basis set, composed of radial functions multiplied by spherical harmonics,…”
Section: B Electronic Charge Densitiesmentioning
confidence: 99%
“…ing of scalar fields such as the electron charge density. Machine-learning models for the charge density have been proposed based on the coefficients in a plane wave basis [16] -this is convenient due to orthogonality, but leads to poor transferability when considering flexible molecules, or learning across different molecular species -or based on direct prediction of the density on a realspace grid [17,36]. By expanding the density on an atomcentred basis set, composed of radial functions multiplied by spherical harmonics,…”
Section: B Electronic Charge Densitiesmentioning
confidence: 99%
“…The advent of big data analytics and machine learning has brought to the forefront a new generation of powerful atomistic and molecular models [23,24,25,26,27,28,29]. This has recently propelled the development of AI-assisted or machine learning based FF that have displayed the promise of bridging the accuracy(fidelity)/flexibility gap between the AIMD and classical/coarse-grained models, while being sufficiently rapid to reach larger length and time scales.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to recognize similarities and differences in the requirements that can be addressed via ML among different applications.In this Perspective, we survey recent uses of ML techniques to solve the Schrödinger equation, including the vibrational Schrödinger equation and the electronic problem: the electronic Schrödinger equation and the related problems of constructing exchange-correlation and kinetic energy functionals for Kohn-Sham (KS-) and orbital-free (OF-) density functional theory (DFT) as well as use of ML for semi-empirical approximations used in density functional based approaches such as DFTB (density functional tight binding) and dispersion-corrected DFT (DFT-D). We only consider the use of ML for the solution of the vibrational and electronic SE or the KS equation or the Hohenberg-Kohn (HK) equation and not methods that aim to avoid such solutions (such as those directly mapping the molecular structure to the spectrum or energy or properties without solving for the density or wavefunction [29][30][31][32][33][34][35][36]); we also do not consider uses of ML for other types of quantum mechanical modelling or other types of differential or integral equations [37][38][39][40][41][42].We do not aim to present a comprehensive review but rather a survey allowing similarities and differences of ML uses in all these applications, as well as promising directions for future research, to transpire. This is not a review of ML methods; the key machine learning techniques that found use in quantum chemistry are well reviewed elsewhere [3-5, 43, 44], their description will not be repeated there; the reader is advised to consult the literature for their introduction, such as [45,46] for neural networks, [47,48] for Gaussian process regression (GPR), [49] for kernel ridge regression (KRR; note the similarity in the form of the function representation between GPR and KRR), [50] for genetic algorithms (GA) and [51] for particle swarm optimization.…”
mentioning
confidence: 99%
“…In this Perspective, we survey recent uses of ML techniques to solve the Schrödinger equation, including the vibrational Schrödinger equation and the electronic problem: the electronic Schrödinger equation and the related problems of constructing exchange-correlation and kinetic energy functionals for Kohn-Sham (KS-) and orbital-free (OF-) density functional theory (DFT) as well as use of ML for semi-empirical approximations used in density functional based approaches such as DFTB (density functional tight binding) and dispersion-corrected DFT (DFT-D). We only consider the use of ML for the solution of the vibrational and electronic SE or the KS equation or the Hohenberg-Kohn (HK) equation and not methods that aim to avoid such solutions (such as those directly mapping the molecular structure to the spectrum or energy or properties without solving for the density or wavefunction [29][30][31][32][33][34][35][36]); we also do not consider uses of ML for other types of quantum mechanical modelling or other types of differential or integral equations [37][38][39][40][41][42].…”
mentioning
confidence: 99%